Real‐time bowel sound analysis using newly developed device in patients undergoing gastric surgery for gastric tumor. Issue 4 (26th February 2021) - Namikawa, Tsutomu; Yamaguchi, Sachi; Fujisawa, Kazune; Ogawa, Maho; Iwabu, Jun; Munekage, Masaya; Uemura, Sunao; Maeda, Hiromichi; Kitagawa, Hiroyuki; Kobayashi, Michiya; Matsuda, Kenichi; Hanazaki, Kazuhiro
Abstract: Background and Aim: Objective measurements are not available for determining bowel sounds. The present study sought to evaluate the efficacy of a novel bowel sound monitoring system for perioperative use in patients undergoing gastric surgery. Methods: The study enrolled 14 patients who underwent surgery for gastric cancer at Kochi Medical School from 2017 to 2018. Preoperative and postoperative bowel sounds were recorded using a newly developed real‐time analysis system in the operating theater and recovery room. Clinical information and bowel sound count data were obtained to compare preoperative and postoperative measures. Results: The median preoperative and postoperative bowel sound counts across all patients were 1.4 and 2.5 counts per minute (cpm), respectively. In patients who underwent laparoscopic gastrectomy, the postoperative bowel sound count was significantly higher than that recorded preoperatively (2.3 vs. 1.6 cpm, P = 0.005). The findings also revealed a significant negative correlation between postoperative bowel sound count and operation time ( r = −0.714, P = 0.003). Conclusions: The real‐time bowel sound analysis system tested herein presents a promising diagnostic tool to quantitatively evaluate bowel movements associated with surgery. Our results suggested a need for shorter operation times for gastric procedures with respect to peristalsis recovery and supported the use of minimally invasive surgery. Abstract : We prospectively evaluated bowel sound counts using newly developed analysis system in patients who underwent gastric surgery. A real‐time bowel sound analysis system is promising as a diagnostic tool to quantitatively evaluate bowel movement. In this study, analysis of bowel sounds in patients undergoing gastrointestinal surgery suggested a need for shorter operation times from the aspect of peristalsis recovery and supporting the use of minimally invasive surgery.